2022
DOI: 10.1007/s11031-022-09977-8
|View full text |Cite
|
Sign up to set email alerts
|

Don’t give up? It’s a little complicated: Action Crisis Moderates Consequences of goal support

Abstract: Social support for goals can be beneficial for goal pursuit, but often has unintended negative consequences for the recipient. We propose that action crisis—the state in which an individual is considering disengaging from a goal they are currently pursuing—may result in people experiencing more ambivalent reactions to goal support. Drawing on both experimental and longitudinal methods, we show that action crisis increases negative consequences of goal support, but does not reduce positive consequences of goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…The finding that an action crisis has negative correlations with same‐day progress towards goals, goal‐directed effort and positive emotions and positive correlations with negative emotions on the same day supports our hypotheses and aligns with prior studies (Brandstätter et al., 2013; Light & Chodos, 2022). It supports the assumption that the experience of an action crisis is unpleasant and accompanies difficulties in the process of goal pursuit.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that an action crisis has negative correlations with same‐day progress towards goals, goal‐directed effort and positive emotions and positive correlations with negative emotions on the same day supports our hypotheses and aligns with prior studies (Brandstätter et al., 2013; Light & Chodos, 2022). It supports the assumption that the experience of an action crisis is unpleasant and accompanies difficulties in the process of goal pursuit.…”
Section: Discussionsupporting
confidence: 91%
“…Also Light and Chodos (2022) highlighted action crises and focused on the affective consequences of receiving social support in that situation. They found that social support during an action crisis predicted negative emotions and depressive symptoms-which have been shown to systematically influence effort and disengagement by increasing the level of subjective demand (see ).…”
Section: Action Crisesmentioning
confidence: 99%
“…As such, romantic partners serve as role models for persisting (or not) in goal pursuit, but also in disengaging from futile tasks. Moreover, social support may have more negative consequences during an action crisis than otherwise, while, at the same time, not having fewer positive consequences either (Light & Chodos, 2022). Again, future research should aim at comparing the impact of social relationships for action crises with actual goal disengagement and examine social support explicitly directed at goal disengagement in contrast to supporting goal pursuit.…”
Section: Summary and Future Directionsmentioning
confidence: 99%